Numerical simulation of geometry effect on mixing performance in L-shaped micromixers. Issue 5 (3rd May 2020) - Zare, Parvaneh; Talebi, Shahram
Abstract: This study accomplishes a numerical analysis of mixing in a microchannel with repeating L-shaped units in order to research the effect of the extension of L-shaped units in a three-dimensional (3D) space and the angle of repeating units on the process of mixing. In the first part, Geometry 2 and Geometry 3 are designed by extending the units of Geometry 1 in a 3D space. In the second part, an L-shaped micromixer, a 90° V-shaped micromixer, and a 60° V-shaped micromixer are analyzed. It is observed that Geometry 1 and Geometry 2 perform better than Geometry 3 in terms of mixing due to the spiral path with 360° rotation of the flow. The L-shaped micromixer is more efficient than the 90° and 60° V-shaped micromixers. A maximum mixing index of about 88% is achieved in all serpentine microchannels at the following Reynolds numbers: Re = 150 and Re = 200.